Inheritance of Ehlers-Danlos type IV syndrome. - Pope, F M (1977)
The Ehlers-Danlos type IV syndrome is a severe disease with premature death from catastrophic tearing of large arteries and a tendency to intestinal rupture. These patients lack the genetically distinct type III collagen. Here evidence is presented that obligate heterozygotes have lowered levels of type III collagen in their skin and that their cultured fibroblasts produce less than normal amounts of this protein. The inheritance is autosomal recessive.